Identification of Climate and Genetic Factors That Control Fat Content and Fatty Acid Composition of Theobroma cacao L. Beans - Mustiga, Guiliana M.; Morrissey, Joe; Stack, Joseph Conrad; DuVal, Ashley; Royaert, Stefan; Jansen, Johannes; Bizzotto, Carolina; Villela-Dias, Cristiano; Mei, Linkai; Cahoon, Edgar B.; Seguine, Ed; Marelli, Jean Philippe; et al. (Frontiers in Plant Science, 2019)
The main ingredients of chocolate are usually cocoa powder, cocoa butter and sugar. Both the powder and the butter are extracted from the beans of the cacao tree (Theobroma cacao L.). The cocoa butter represents the fat in the beans and possesses a unique fatty acid profile that results in chocolate’s characteristic texture and mouthfeel. Here, we used a linkage mapping population and phenotypic data of 3,292 samples from 420 progeny which lead to the identification of 27 quantitative trait loci (QTLs) for fatty acid composition and six QTLs for fat content. Progeny showed extensive variation in fat levels and composition, with the level of palmitic acid negatively correlated to the sum of stearic acid, oleic acid, and linoleic acid. A major QTL explaining 24 percent of the relative level of palmitic acid was mapped to the distal end of chromosome four, and those higher levels of palmitic acid were associated with the presence of a haplotype from the ‘TSH 1188’ parent in the progeny. Within this region of chromosome four is the Thecc1EG017405 gene, an orthologue and isoform of the stearoyl-ACP desaturase (SAD) gene in plants, which is involved in fatty acid biosynthesis. Besides allelic differences, we also show that climate factors can change the fatty acid composition in the beans, including a significant positive correlation between higher temperatures and the higher level of palmitic acid. Moreover, we found a significant pollen donor effect from the variety ‘SIAL 70’ which was associated with decreased palmitic acid levels.